(untitled) (Fiep Bulletin - online, 2015)
Introduction: Hypertension is seen as a public health problem and cardiovascular disease that affects mostly the male population. Objective: To evaluate the satisfaction of care offered to man hypertensive patients in primary care. Methods: cross-sectional study of exploratory, with quantitative approach developed in Cajazeiras/PB with 231 hypertensive men enrolled and registered in seven Health Units of the Family, in the period of May 2012. Results: The subjects of the study had an average of 62.27 years, with 61.3% of the sample above this value characterizing a group of elderly population. The hypertensive patients in 67.5% were satisfied with the assistance and 33.5% expressed the need to receive more information during the consultations and the development of educational activities (29.3 % ); The record of consultation was carried out predominantly in the card of the hypertensive (50 % ). Conclusion: it is necessary for health professionals to rethink practices devoted to assistance to man hypertensive, and that managers invest more in training and quality provided.